28 Using experimental simulation of dementia to understand functional cognitive disorders. (28th May 2019) - Sargent, Brendan; McWhirter, Laura; Stone, Jon; Carson, Alan
Abstract : Objectives/Aims: Symptoms and signs of functional (psychogenic) motor and sensory disorder often depend on the individual's ideas about symptoms rather than on the rules of anatomy and physiology. The possibility that functional cognitive symptoms might similarly reflect beliefs about cognitive disorders such as dementia has not been widely explored. We aimed to assess the ideas and beliefs of healthy non- medical adults about symptoms of mild dementia. Methods: Healthy adult volunteers aged 18-27, without medical training, underwent a 25 minute assessment during which they were asked to imagine that they in fact had symptoms of 'mild or early stage dementia'. The assessment included the Montreal Cognitive Examination (MOCA), examination of gait, digit span, the Luria 3-step test, interlocking finger test of parietal function, and the 'coin in hand' forced-choice test. Close family history of dementia and specific perceptions about dementia were recorded. Results: In 50 participants, mean age 22, mean MOCA score was 16 (SD 5.5, range 5 – 26). Summed responsetime ranged from 5 minutes 13 seconds to 14 minutes 12 seconds (mean 8 minutes 4 seconds, SD 1 minute 59 seconds). Delayed recall was the most frequently failed item (100%) followed by letter vigilance (86%), forward 5-digit span (82%) and clock-drawing (82%). Cube drawing was the least frequently failed item (42%). 26% failed forward 3-digit span and 36% failed reverse 2-digit span. On the 'coin in hand' test, 30% scored at (22%) or below (8%) the level of chance. 18% successfully completed the Luria 3-step test. 76% successfully copied 3 or 4 interlocking finger positions. 48% had abnormal gait. Inconsistent response patterns and difficulty following and remembering instructions was common. There were no significant differences between those with and without a family history of dementia. Conclusions: Cognitively healthy young adults simulating mild dementia perform similarly to older adults with mild dementia, demonstrating beliefs that dementia is associated with significant global impairment, including of attention and motor function, with relatively poor performance on letter vigilance, but preservation of cube drawing. Inconsistent response patterns were common. Contrary to expectation, family history of dementia did not influence performance. Digit span showed particular promise as a bedside test. Further investigation will establish whether similar patterns of results are produced in individuals with functional cognitive symptoms.